Analisis Maqashid Al-Syariah Terhadap Tingginya Angka Perceraian di Indonesia - Ananda Rizky Pratama; Nabil Hidayah; Amanda Septiani; Rince Anggraini; Siti Aliya Sabrinah; Suci Andini (CV. Doki Course and Training, 2025)
The high divorce rate in Indonesia is a multidimensional phenomenon influenced by economic factors, prolonged conflict, unpreparedness of partners, domestic violence, weak understanding of marital values, and social and cultural changes. This study uses a qualitative approach with a juridical-normative framework, analyzing these factors through the perspective of Maqashid al-Syariah. The results of the analysis indicate that these factors have the potential to threaten the achievement of the main goals of marriage, namely creating sakinah, mawaddah, and rahmah, as well as maintaining the five basic principles of sharia: religion (ḥifẓ al-dīn), soul (ḥifẓ al-nafs), reason (ḥifẓ al-‘aql), descendants (ḥifẓ al-nasl), and property (ḥifẓ al-māl). Divorce prevention requires a comprehensive approach that includes premarital education, internalization of marital values, strengthening communication, conflict management, and protecting the rights of family members. Divorce should be used as the ultimum remedium when all preventive efforts have failed, so that the principles of Maqashid remain protected and the goals of marriage can be achieved optimally.